Colonia Augusta Firma – Astigi (Écija, Seville): New Archaeological and Epigraphical Evidence - Salvador Ordóñez Agulla; Sergio García-Dils de la Vega (Gerión, 2018)
This paper offers a summary of the latest outcomes of archaeological excavations that are being carried out in the plaza de Armas of the old town’s alcázar. Contributions provided by epigraphic recent news are added to this panorama, incorporating some unpublished pieces.